1997
DOI: 10.1177/0333102497017s1804
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug interactions with the novel antimigraine compound zolmitriptan (Zomig™, 311C90)

Abstract: Seven randomized studies in healthy volunteers have investigated interactions between zolmitriptan (Zomig, formerly 311C90), a 5HT1B/1D agonist for acute migraine therapy, and selected drugs with which there was a possibility of interaction or a likelihood of concurrent use. Co-administration of oral dihydroergotamine, ergotamine, pizotifen, fluoxetine, paracetamol (acetaminophen)/metoclopramide or selegiline had no clinically significant effects on the pharmacokinetics of zolmitriptan or its metabolites, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…56 No clinically signifi cant interactions with other commonly prescribed medications in headache management such as metoclopramide, dihydroergotamine, fl uoxetine, and propranolol, or monoamine oxidase-B inhibitors such as selegiline, have been demonstrated. 56,57 However, it is contraindicated to give zolmitriptan to a patient on MAO-A inhibitor or within 24 hours of use of an ergot or another triptan. 59,60 In addition, it has been demonstrated that cimetidine inhibits the metabolism of zolmitriptan and its active metabolite, increasing the mean Cmax by 16 and 50% and the mean AUC by 48 and 105%, respectively.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…56 No clinically signifi cant interactions with other commonly prescribed medications in headache management such as metoclopramide, dihydroergotamine, fl uoxetine, and propranolol, or monoamine oxidase-B inhibitors such as selegiline, have been demonstrated. 56,57 However, it is contraindicated to give zolmitriptan to a patient on MAO-A inhibitor or within 24 hours of use of an ergot or another triptan. 59,60 In addition, it has been demonstrated that cimetidine inhibits the metabolism of zolmitriptan and its active metabolite, increasing the mean Cmax by 16 and 50% and the mean AUC by 48 and 105%, respectively.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…183C91 has plasma concentrations on average around one-half to two-thirds of those of the parent compound [2]. Cytochrome P 450 (CYP) 1A2 is responsible for the biotransformation of zolmitriptan to 183C91 [3], which in turn is further metabolised to the inactive indole acetic acid metabolite by monoamine oxidase type A [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main reported interaction between drugs assumed for symptomatic treatment and prophylactic drugs is that between propranolol and zolmitritpan. The drug-drug interaction is, however, not clinically significant when patients use a dose of 2.5 mg, as usually done in Italy [29]. From a pharmacodynamic point of view, the co-assumption of a triptan and a serotoninergic drug, like most antidepressant drugs used in headache prophylaxis, increases the risk of developing a serotoninergic syndrome [30].…”
Section: Comorbidities and Drug-drug Interactionsmentioning
confidence: 99%